Characterization of the complete mitochondrial genome of Aspergillus terricola (Aspergillaceae, Eurotiales), isolated from soy sauce fermentation system - Yue Deng; Jie He (Mitochondrial DNA. Part B. Resources, 2022)
In the present study, the complete mitochondrial genome of Aspergillus terricola É.J. Marchal 1893 was sequenced and assembled. The mitochondrial genome of A. terricola was composed of circular DNA molecules, with a total size of 28,689 bp. The GC content of the A. terricola mitochondrial genome was 26.34%. A total of 18 protein-coding genes (PCGs), 2 ribosomal RNA (rRNA) genes, and 26 transfer RNA (tRNA) genes were detected in the A. terricola mitochondrial genome. Phylogenetic analysis based on the combined mitochondrial gene dataset indicated that the A. terricola exhibited a close relationship with A. parasiticus.